Voluntarily wheel running inhibits the growth of CRPC xenograft by inhibiting HMGB1 in mice - Zhaoyun Yang; Yan Gao; Kang He; Xin Sui; Junyu Chen; Taiwei Wang; Mengmeng Chen; Zeyu Wang; Jiang Yi; Lijing Zhao (Experimental Gerontology, 2023)
Introduction: Exercise has been proved to reduce the risk of recurrence and mortality of cancer. Emerging evidence indicated that exercise may regulate both systematical and local metabolism, immunity and other ways. Although the role of exercise in inhibiting castration-resistant prostate cancer is well established, the underlying mechanism remains unclear. Method: Twenty C57BL/6 male mice were used to construct CRPC xenograft models and randomly divided into exercise group (n = 10) and control group (n = 10). After exercised with voluntarily wheel running for 21 days, the mice were sacrificed and the tumor tissues and serum were collected. TUNEL staining was used to detect the apoptosis of tumor cells. The expression of PI3K signal pathway and apoptosis related proteins were detected by Western blot. The expression of AR and HMGB1 were examined by Western blot and Immunohistochemical staining. IFN-γ, TNF-α, TGF-β, IL-4, IL-6, IL-10 in serum was examined using ELISA kits. Results: Voluntarily wheel running inhibited the growth of CRPC xenografts, inhibited the proliferation of tumor cells and promoted the apoptosis of tumor cells. HMGB1 levels in serum and tumor tissues were significantly reduced after exercise, which enhanced local immunity by inducing more leukocyte infiltration and inhibited systemic inflammatory response by regulating cytokines. Conclusion: Voluntary wheel running can down-regulate the expression of HMGB1 in serum and transplanted tumor tissues, inhibit proliferation and promote apoptosis of tumor cells, enhance immune cell infiltration and systemic inflammatory response, and regulate local anti-tumor effects in tumor microenvironment.